2019
DOI: 10.33429/cjas.10119.4/6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Trade Openness on Economic Growth among ECOWAS Countries: 1975-2017

Abstract: This study assesses the impact of trade openness on economic growth among ECOWAS countries uses secondary data from 1975 to 2017. The study uses non-stationary heterogeneous dynamic panel models through the application of Pooled Mean Group (PMG) and Mean Group (MG) estimators since time dimension was more than cross-sections. Using the Hausman test, PMG estimator was preferred. Results show that trade openness has positive effects on growth in ECOWAS countries in the long-run but mixed effects in the short-run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
(16 reference statements)
1
13
1
Order By: Relevance
“…In Asian countries, Bajwa and Siddiqi [51] confirmed that three countries have a negative and statistically significant relationship with GDP in the years 1972 to 1985, while it was positive for Pakistan, and from 1986 to 2007 all countries had a positive effect on economic growth. In the case of Economic Community of West African States (ECOWAS) countries, a significant and positive relationship between trade openness and economic growth was observed [52]. Another remarkable study by Nguyen [53] conducted in three Northeast Asian countries found that trade openness accelerates the level of economic growth.…”
Section: Introductionmentioning
confidence: 97%
“…In Asian countries, Bajwa and Siddiqi [51] confirmed that three countries have a negative and statistically significant relationship with GDP in the years 1972 to 1985, while it was positive for Pakistan, and from 1986 to 2007 all countries had a positive effect on economic growth. In the case of Economic Community of West African States (ECOWAS) countries, a significant and positive relationship between trade openness and economic growth was observed [52]. Another remarkable study by Nguyen [53] conducted in three Northeast Asian countries found that trade openness accelerates the level of economic growth.…”
Section: Introductionmentioning
confidence: 97%
“…GDP is determined every year, sometimes referred to as Annual GDP. The annual GDP is the total monetary worth of a country's final products and services at market prices for a particular year (Ijirshar, 2019). The Gross Domestic Product, also abbreviated as GDP, is one of the vital tools used by economists to measure or gauge the production level of any economy or the strength of any economy.…”
Section: Gdpmentioning
confidence: 99%
“…According to (Ijirshar 2019), the total earnings, stock capital, and other capital reinvestment are referred to as foreign direct investments. All those Investments in the boundaries of a country are considered the Foreign Direct Investment (FDI) if the 10% or more equity shares of that investment belong to the people who are not the residents of that country.…”
Section: Fdimentioning
confidence: 99%
See 1 more Smart Citation
“…Many benefits will be obtained through international trade, including obtaining goods that cannot be produced at home, benefiting from specialization, and technology transfer (Makhmutova & Mustafin, 2017;Elias et al, 2018). However, international trade can become an obstacle to high economic growth if a growing number of imports is not accompanied by an increase in exports with a flat growth rate (Ijirshar, 2019). Reduced national income due to an increase in imports is more significant than the increase in national income due to an increase in exports will cause a decline in economic growth.…”
Section: Introductionmentioning
confidence: 99%